An experimental study for determination of an application method and TiO2 powder to ensure the thinnest matte coating layer for 3D optical scanning. (March 2019) - Hruboš, David; Koutecký, Tomáš; Paloušek, David
Highlights: Matte coating used for optical 3D scanning was investigated. The goal was to produce thinnest possible layer with sufficient covering effect. Three different TiO2 powders and two spraying guns were tested. Spraying was affected by agglomeration and sedimentation of TiO2 primary particles. Coating layer with thickness of 200–600 nm was produced by both guns. Abstract: This paper deals with matte coatings for 3D optical scanning and the aim is to find a method of spraying the mixture of TiO2 and ethanol that would provide layer thickness below the measurable range of commonly used industrial 3D scanners. A spray gun allowing a deposition of atomized mixture was designed. The coatings created by this gun and by airbrush gun, which is commonly used for this purpose, were compared. The matting effect, thickness, and the influence of diverse TiO2 particles were investigated in the coatings. The paper shows the method of applying the coatings that ensure sufficient matting of the surface for scanning purposes and, along with this, they have thicknesses that should not affect scanning results.